12-O-Tetradecanoylphorbol-13-acetate increases cardiomyogenesis through PKC/ERK signaling - Radaszkiewicz, Katarzyna Anna; Beckerová, Deborah; Woloszczuková, Lucie; Radaszkiewicz, Tomasz Witold; Lesáková, Petra; Blanářová, Olga Vondálová; Kubala, Lukáš; Humpolíček, Petr; Pachernik, Jiří (Scientific reports, 2020)
12-O-Tetradecanoylphorbol-13-acetate (TPA) is the most widely used diacylglycerol (DAG) mimetic agent and inducer of protein kinase C (PKC)-mediated cellular response in biomedical studies. TPA has been proposed as a pluripotent cell differentiation factor, but results obtained have been inconsistent. In the present study we show that TPA can be applied as a cardiomyogenesis-promoting factor for the differentiation of mouse embryonic stem (mES) cells in vitro. The mechanism of TPA action is mediated by the induction of extracellular signal-regulated kinase (ERK) activity and the subsequent phosphorylation of GATA4 transcription factor. Interestingly, general mitogens (FGF, EGF, VEGF and serum) or canonical WNT signalling did not mimic the effect of TPA. Moreover, on the basis of our results, we postulate that a TPA-sensitive population of cardiac progenitor cells exists at a certain time point (after days 6-8 of the differentiation protocol) and that the proposed treatment can be used to increase the multiplication of ES cell-derived cardiomyocytes.
Keywords: signální transdukce; Cell Differentiation; Tetradecanoylphorbol Acetate; Phosphorylation; Signal Transduction; Mice; Myocytes, Cardiac; Embryonic Stem Cells; embryonální kmenové buňky; Extracellular Signal-Regulated MAP Kinases; zvířata; proteinkinasa C; myši; extracelulárním signálem regulované MAP kinasy; tetradekanoylforbolacetát; kardiomyocyty; buněčná diferenciace; fosforylace; Protein Kinase C; Animals